Ética e ontologia em Lukács e o complexo social da educação - Mônica Tassigny Mota (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
The problems related to the phenomenon of education have given rise, in the current historical moment, to growing interest, marked by the general structural crisis of the material production of the form of sociability conducted by capital, which results in profound crises in varied instances of society. This results in the need to surpass, in the educational field, old unilateral visions of contemporary educational phenomena. Independent of the place which it is given from a social and historical point of view, the social complex of education is constituted, from the ethical-ontological perspective of Georg Lukács, as a rich, complex and contradictory fact, which it is not possible to approach without a solid theoretical-methodological basis.